Dental wear estimation using a digital intra-oral optical scanner and an automated 3D computer vision method. Issue 5 (3rd April 2016) - Meireles, Agnes Batista; Vieira, Antonio Wilson; Corpas, Livia; Vandenberghe, Bart; Bastos, Flavia Souza; Lambrechts, Paul; Campos, Mario Montenegro; Las Casas, Estevam Barbosa de
Abstract : The objective of this work was to propose an automated and direct process to grade tooth wear intra-orally. Eight extracted teeth were etched with acid for different times to produce wear and scanned with an intra-oral optical scanner. Computer vision algorithms were used for alignment and comparison among models. Wear volume was estimated and visual scoring was achieved to determine reliability. Results demonstrated that it is possible to directly detect submillimeter differences in teeth surfaces with an automated method with results similar to those obtained by direct visual inspection. The investigated method proved to be reliable for comparison of measurements over time.